Amniotic fluid markers of oxidative stress in pregnancies complicated by preterm prelabor rupture of membranes - Kacerovsky, Marian; Tothova, Lubomira; Menon, Ramkumar; Vlkova, Barbora; Musilova, Ivana; Hornychova, Helena; Prochazka, Martin; Celec, Peter (The journal of maternal-fetal & neonatal medicine, 2015)
OBJECTIVE: To determine amniotic fluid total antioxidant capacity (TAC), ferric-reducing antioxidant power (FRAP) and thiobarbituric acid-reacting substances (TBARS), markers of oxidative stress, in pregnancies complicated by preterm prelabor rupture of membranes (pPROM) and their correlation to microbial invasion of the amniotic cavity (MIAC) and/or histological chorioamnionitis (HCA). METHODS: One-hundred thirty-eight women with singleton pregnancies complicated by pPROM were included in this study. Amniotic fluid was collected by transabdominal amniocentesis at the time of admission and amniotic fluid concentrations of TAC, FRAP and TBARS were measured. RESULT: The presence of MIAC and/or HCA did not show any significant differences in the amniotic fluid TAC, FRAP and TBARS concentrations. Positive correlations between gestational age at sampling and amniotic fluid TAC and FRAP concentrations were found (TAC: rho = 0.32; p = 0.0002; FRAP: rho = 0.36; p < 0.0001). A negative correlation between gestation age at sampling and amniotic fluid TBARS concentrations was identified (rho = -0.25; p = 0.004). CONCLUSIONS: Oxidative stress is associated with pPROM as indicated by the presence of markers tested in the amniotic fluid; however, oxidative stress markers tested are not influenced by the presence of MIAC or HCA.
Keywords: inflammation; Infection; preterm delivery